Analisis Pengaruh Pendapatan Perkapita dan Inflasi terhadap Pengeluaran Konsumsi Rumah Tangga di Provinsi Jambi - Ahmad Soleh; Prima Audia Daniel; Mukti Said; Kiki Agustina (Universitas Batanghari, 2023)
This research aims to determine and analyze developments in per capita income, inflation and household consumption expenditure in Jambi Province. To determine and analyze the influence of per capita income and inflation on household consumption expenditure in Jambi Province. The research method used is secondary data analysis with the research objective being a quantitative descriptive analysis method to answer the first objective, to see the development of per capita income, inflation and household consumption expenditure in Jambi Province during the 2008-2022 period using the development formula. Meanwhile, to see the effect of per capita income and inflation on household consumption expenditure in Jambi Province, multiple linear regression was used with the help of the SPSS software application analysis tool. The results of the analysis carried out concluded, firstly, that the development of per capita income, inflation and household consumption expenditure in Jambi Province for the 2008-2022 period was relatively increasing. Kudua, namely that partially the per capita income variable has a significant effect on household consumption expenditure, while inflation has no significant effect on household consumption expenditure in Jambi Province. However, simultaneously per capita income and inflation have a significant effect on household consumption expenditure with an R-square value of 91.90 percent during the 2008-2022 period.